Fertility desires and reproductive needs of transgender people: Challenges and considerations for clinical practice. (17th April 2019) - Feigerlová, Eva; Pascal, Véronique; Ganne‐Devonec, Marie‐Odile; Klein, Marc; Guerci, Bruno
Abstract: The majority of transgender and gender nonconforming persons seeking medical care are of reproductive age. Hormonal treatment and sex reassignment surgery, which are used in the management of gender dysphoria, compromise fertility potential. Children and adolescents with gender dysphoria have specific treatment regimens starting with puberty‐blocking medications. According to international guidelines, fertility preservation should be discussed before any hormonal treatment, although our knowledge on the reproductive needs of transgender and gender nonconforming persons is limited. Recently, some data have emerged on fertility management in some centres for the adult population with gender dysphoria. The goal of this review was to summarize the available evidence on the fertility desires and parental roles of transgender and gender nonconforming people. In light of newly emerging societal challenges, we aim to provide some considerations for clinical practice and suggest further areas of research.